2012
DOI: 10.1093/jac/dks147
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin is a potent inhibitor of flavivirus replication specifically targeting NS3 helicase activity: new prospects for an old drug

Abstract: The well-tolerated drug ivermectin may hold great potential for treatment of YFV infections. Furthermore, structure-based optimization may result in analogues exerting potent activity against flaviviruses other than YFV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
290
0
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(319 citation statements)
references
References 48 publications
4
290
0
15
Order By: Relevance
“…1 C-D), thus it can be assumed that EHV-1 was not dependent on the exportin 1-mediated nuclear export. Many studies have previously confirmed that ivermectin is able to inhibit replication of HIV-1, dengue virus and West Nile virus (Mastrangelo et al 2012, Wagstaff et al 2012. It has been demonstrated that ivermectin is affecting NS3 helicase activity, required during viral RNA replication.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…1 C-D), thus it can be assumed that EHV-1 was not dependent on the exportin 1-mediated nuclear export. Many studies have previously confirmed that ivermectin is able to inhibit replication of HIV-1, dengue virus and West Nile virus (Mastrangelo et al 2012, Wagstaff et al 2012. It has been demonstrated that ivermectin is affecting NS3 helicase activity, required during viral RNA replication.…”
Section: Resultsmentioning
confidence: 98%
“…Receptor-mediated nuclear import and export is utilized by adenoviruses, parvoviruses, flaviviruses, retroviruses and herpesviruses and disruption of specific nuclear transport pathways is crucial for the efficacious replication cycle (Greber and Correspondence to: A. Słońska, e-mail: anex007@op.pl, tel. : 22 593 60 55 Fornerod, 2004, Mastrangelo et al 2012, Wagstaff et al 2012. In the present study, we have used two inhibitors -ivermectin as an importin α/β inhibitor and leptomycin B as an exportin 1 inhibitor to determine their effect on EHV-1 replication in primary murine neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Aglycon, an analog of teicoplanin was shown to be active on DENV, yellow fever, tick-borne encephalitis, Japanese encephalitis (JEV) and murine flavivirus Modoc viruses; ivermectin on CHIKV, yellow fever , dengue, Japanese encephalitis, tick-borne encephalitis, West Nile , CHIKV, Semliki Forest (SFV), and Sindbis viruses; niclosamide on JEV; abamectin on CHIKV; and AZ on ZIKV [6,7,9,11,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…It also inhibits replication in several other flaviviruses, including dengue, Japanese encephalitis and tick-borne encephalitis, probably by targeting non-structural 3 helicase activity. 97 Ivermectin inhibits dengue viruses and interrupts virus replication, bestowing protection against infection with all distinct virus serotypes, and has unexplored potential as a dengue antiviral. 98 Ivermectin has also been demonstrated to be a potent broadspectrum specific inhibitor of importin α/β-mediated nuclear transport and demonstrates antiviral activity against several RNA viruses by blocking the nuclear trafficking of viral proteins.…”
Section: Asthmamentioning
confidence: 99%